2021
DOI: 10.1039/d1ra04756f
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biological assessment and in silico ADME prediction of new 2-(4-(methylsulfonyl) phenyl) benzimidazoles as selective cyclooxygenase-2 inhibitors

Abstract: A novel series of benzimidazole derivatives wherein 4-(methylsulfonyl) phenyl pharmacophore attached via its C-2 position was designed and synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Using the PyMOL (v0.99) program, 3D interactions between ligands and proteins were clarified. [ 98 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the PyMOL (v0.99) program, 3D interactions between ligands and proteins were clarified. [ 98 ]…”
Section: Methodsmentioning
confidence: 99%
“…In addition, evaluating other parameters, such as the calculation of topological polar surface area (TPSA) (a parameter that enables the prediction of transport properties of polar atoms through membranes), has proven useful as a virtual screening tool. [98] Herein, the physicochemical properties, pharmacokinetics, and drug-likeness profile for compound 5e were estimated using pkCSM online software pkCSM (unimelb.edu.au). (human colon adenocarcinoma) permeability coefficient model generates a tight junction between compounds' movement and transport across a monolayer.…”
Section: Absorption Distribution Metabolism Excretion and Toxicity (A...mentioning
confidence: 99%
“…Cyclo-oxygen-ase-2 (COX-2) is widely involved in the inflammatory response and plays a crucial role in the inflammatory pathway, which can be improved by inhibiting it with NSAIDS, which can reduce the production of key pro-inflammatory mediators PG by inhibiting COX-1 and COX-2 ( 114 ). Long-term use of NSAIDS predisposes to gastrointestinal and cardiovascular diseases, which may be caused by gastric, renal, and platelet cell dysfunction due to COX-1 inhibition ( 115 ). Through research experts have found that selective COX-2 inhibitors have less side effects than non-selective COX-2 inhibitors.…”
Section: Cyclo-oxygen-ase-2 Inhibitorsmentioning
confidence: 99%